2017
DOI: 10.1177/0261018317745609
|View full text |Cite
|
Sign up to set email alerts
|

The role of discourse in family policy reform: The case of Finland

Abstract: Since 2011 and the onset of the economic crisis, Finnish governments have pressed for structural reforms, including unpopular cuts to family benefits and services. This article analyses the government discourse used for legitimating some of these reforms: the cutbacks in the child benefit and the restriction of full-time childcare. It also assess whether this discourse bore the hallmarks of a neoliberal austerity discourse, which could suggest that the reforms were not just a matter of fiscal balancing but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
0
19
0
3
Order By: Relevance
“…A number of studies (e.g. Blum, Formánková, & Dobrotic, 2014;Chzhen, Nolan, Cantillon, & Handa, 2017;Nyby et al, 2017;O'Hara, 2015) have shown this to be the case in most European countries after the 2008-2009 financial crisis. If the NAP recognises social risks, these are more likely to be 'old' social risks, but since the main creed of NAP is for people to be self-sufficient, and welfare benefits to be directed only to the (undeserving) poorest, risk conceptualisations of this kind are rather unlikely in the first place.…”
Section: The Role Of Ideas and Narrative Stories In Policymakingmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies (e.g. Blum, Formánková, & Dobrotic, 2014;Chzhen, Nolan, Cantillon, & Handa, 2017;Nyby et al, 2017;O'Hara, 2015) have shown this to be the case in most European countries after the 2008-2009 financial crisis. If the NAP recognises social risks, these are more likely to be 'old' social risks, but since the main creed of NAP is for people to be self-sufficient, and welfare benefits to be directed only to the (undeserving) poorest, risk conceptualisations of this kind are rather unlikely in the first place.…”
Section: The Role Of Ideas and Narrative Stories In Policymakingmentioning
confidence: 99%
“…Béland, 2010;Cox, 2001;Hall, 1993;Schmidt, 2008) and narrative stories (Czarniawska, 2004;Stone, 2012) with insights from the family policy literature (e.g. Nyby et al, 2018;Nyby, Nygård, Autto, Kuisma, & Blum, 2017;Thévenon, 2018;Björk Eydal et al, 2018;Van Gerven & Nygård, 2017;Kuebler, 2007). Ideas and narrative stories are essential for the social construction of the world (Berger & Luckman, 1966), but can also serve as legitimising devices when it comes to changes, such as family policy reforms (Kuebler, 2007;Nyby et al, 2017).…”
Section: The Role Of Ideas and Narrative Stories In Policymakingmentioning
confidence: 99%
See 2 more Smart Citations
“…While these factors explain reasons for reform, they do very little for explaining why reforms take a certain shape . Instead, normative ideas on what the welfare state should do, and the discourse used by the governments affect the suggestions for and design of reform (e.g., Béland, ; Schmidt, ; for a discussion on discourse in the case of Finnish family policy see Nyby et al., ), can partly explain why a certain reform is pursued. Normative ideas can, in turn, be linked to political partisanship (e.g., Allan & Scruggs, ), where typically left‐wing parties tend to favor a big welfare state, and right‐wing parties tend to advocate less state regulation.…”
Section: Welfare State Reformmentioning
confidence: 99%